2017
DOI: 10.1016/j.orgel.2017.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature processed NiOx hole transport layers for efficient polymer solar cells

Abstract: We here demonstrate the use of solution processed NiO x thin films as the hole transport layer (HTL) in a thiophene-quinoxaline copolymer:fullerene solar cell. The NiO x films, which are prepared by UV-ozone treating a nickel formate precursor, outperform the solar cells prepared in this study that use PEDOT:PSS as HTL. The power conversion efficiency improves from 5.3% to 6.1% when replacing PEDOT:PSS with NiO x . Unlike most conventional ways of fabricating solution processed NiO x HTLs, our method does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…However, the high‐temperature TA process suffers from high energy cost and is not compatible with flexible devices because general flexible substrates like polyethylene terephthalate (PET) are not able to withstand high‐temperature TA process above 150 °C [18] . Only few metal oxides could be prepared from their precursor solution at low temperature by a post decomposition in the presence of H 2 O 2 or UV‐ozone (UVO) treatment [10d, 11b, 13, 14] . Alterative to the metal oxides, some metal salts has also been applied as HTLs, such as cuprous iodide (CuI) [19] and cuprous thiocyanate (CuSCN) [20] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high‐temperature TA process suffers from high energy cost and is not compatible with flexible devices because general flexible substrates like polyethylene terephthalate (PET) are not able to withstand high‐temperature TA process above 150 °C [18] . Only few metal oxides could be prepared from their precursor solution at low temperature by a post decomposition in the presence of H 2 O 2 or UV‐ozone (UVO) treatment [10d, 11b, 13, 14] . Alterative to the metal oxides, some metal salts has also been applied as HTLs, such as cuprous iodide (CuI) [19] and cuprous thiocyanate (CuSCN) [20] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been extensive studies on solution‐processed NiO x for organic solar cells, with differing polymer blends for the photoactive layer, different solvents for the NiO x precursor, annealing temperature, and post‐deposition treatments. Work function tuning results in values > 5.0 eV and power conversion efficiencies (PCEs) between 3.6% and 7.8% 102,107,172,178,179 . The band alignment for common organic materials with charge transport layers are shown in Figure 11.…”
Section: Nickel Oxide Thin Films In Devicesmentioning
confidence: 99%
“…Work function tuning results in values >5.0 eV and power conversion efficiencies (PCEs) between 3.6% and 7.8%. 102,107,172,178,179 The band alignment for common organic materials with charge transport layers are shown in Figure 11. In addition to solution processing, Shim et al reported the first use of ALD deposited NiO x for polymer solar cells using Ni-AMD (Nickel Alkyl Amidinate) and H 2 O precursor, with a deposition temperature of 150 C. Then, 25 nm films, with a band gap of 3.7 eV, were oxygen plasma treated for 3 minutes following deposition, which increased the work function from 4.7 eV to 5.4 eV with the formation of nickel oxyhydroxide species or nickel vacancies on the surface.…”
Section: Nio X For Flexible Thin-film Transistorsmentioning
confidence: 99%
“…However, the high‐temperature TA process suffers from high energy cost and is not compatible with flexible devices because general flexible substrates like polyethylene terephthalate (PET) are not able to withstand high‐temperature TA process above 150 °C [18] . Only few metal oxides could be prepared from their precursor solution at low temperature by a post decomposition in the presence of H 2 O 2 or UV‐ozone (UVO) treatment [10d, 11b, 13, 14] . Alterative to the metal oxides, some metal salts has also been applied as HTLs, such as cuprous iodide (CuI) [19] and cuprous thiocyanate (CuSCN) [20] .…”
Section: Introductionmentioning
confidence: 99%